PENGATURAN DAN PELAKSANAAN STANDARDISASI USAHA JASA PARIWISATA DI KOTA BUKITTINGGI - Aryati, Rika (MENARA EKONOMI, 2018)
Indonesia is a tourism country. One of the most visited provinces is West Sumatera especially in Bukittinggi. There are many tourism services business here that support tourism activities, because it is one of the most local revenue resources. To achieve a qualified Tourism business services, government should undertake standardization. Thus, this research tries to examine and discuss about Regulation and Implementation of Standardization of Tourism Business Services in Bukittinggi which will answer some problems. They are, how the regulation of standardization nationally and Internationally, how the implementation of standardization regulation and what efforts that have being done by the government to protect the tourists. This is a descriptive study using an empirical juridical method. Some answers that can be conclude are, there is no special regulation that concern on standardization of the tourism business service internationally, and in other hand it is covered by Government Regulation No. 52 of 2012. Bukittinggi has not done the standardization. To protect the tourists the government implements some obligations which must be fulfilled by the businessmen about their services, perform tourism awareness guidance to society and cooperate with the Tourism organization and constabulary in Bukittinggi.Keywords: Standardization; Business; Tourism